Acceleration and deceleration demands of different soccer training drills and competitive matches - Silva, H.; Nakamura, F. Y.; Bajanca, C.; Serpiello, F. R.; Pinho, G.; Marcelino, R. (German Journal of Exercise and Sport Research, 2026)
This study compared acceleration and deceleration demands between different training drills (compensation, rondos, small-sided games, technical) and matches, and between playing positions. Nineteen professional players were monitored during four microcycles. Efforts intensities were classified as low (25-50%), moderate (50-75%), and high (> 75%); starting speed was assessed in bandwidths (< 5 km/h, 5-10km/h, 10-15 km/h, 15-20 km/h, 20-25 km/h, and > 25 km/h). Paired mean differences compared activities, and independent groups contrasts compared playing positions, with 90% confidence intervals. Match elicited more high-intensity accelerations than technical drills (effect size [ES]: 1.75 [1.40, 2.28]), rondos (ES: 1.47 [0.92, 2.17]), compensation drills (ES: 1.28 [0.66, 2.09]), and small-sided games (ES: 0.64 [0.11, 1.25]), and more high-intensity decelerations than technical drills (ES: 0.74 [0.24, 1.32]) and rondos (ES: 0.53 [0.04, 1.06]). Compensation drills elicited more decelerations starting > 25km/h than small-sided games (ES: 2.90 [2.18, 3.98]), technical drills (ES: 2.88 [2.11, 4.02]), and matches (ES: 2.06 [1.35, 3.08]). Fullbacks performed more high-intensity accelerations than central midfielders during small-sided games (ES: 0.10 [0.01, 0.20]), wide midfielders performed more high-intensity accelerations than central defenders during technical drills (ES: 0.05 [0.02, 0.08]), and wide midfielders performed more decelerations starting > 25 km/h than central defenders (ES: 0.10 [0.01, 0.20]) and central midfielders (ES: 0.12 [0.04, 0.20]) during matches. Match imposed higher demands to players than any drill, and merging compensation drills with small-sided games can be a good strategy to compensate competition acceleration and deceleration demands. Rondos drills should be carefully used due to the high deceleration demands.